Pengaruh Lingkungan Kerja Fisik dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan Klinik Pratama Syariah Handira Kota Banjarbaru - Kadir, Abdul; Hanna Mazati (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2022)
The purpose of this study was to determine and partially analyze the effect of Physical Work Environment on Non-Physical Work Environment on the Performance of Handira Syariah Primary Clinic, Banjarbaru City. The type of research used in this research is correlational research with quantitative methods, namely research conducted by collecting data to find out whether there is a relationship between the variables of the Physical Work Environment and Non-Physical Work Environment on the Performance of the Pratama Syariah Handira Clinic in Banjarbaru City. The population of this study were all employees of the Pratama Syariah Handira Clinic, Banjarbaru City, totaling 35 people. The sampling method used in this study is the census method. choosing the census method, where all 35 employees of the Pratama Syariah Handira Clinic, Banjarbaru City, were used as samples. Data collection techniques using questionnaires, documentation, interviews and observation. Validity and reliability tests were carried out on research instruments. Data were analyzed with multiple linear regression analysis with the classical assumption test. The results showed that the physical work environment and non-physical work environment partially had a significant effect on the Employee Performance of the Pratama Syariah Handira Clinic, Banjarbaru City.